2021
DOI: 10.1177/0003489421995038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mast Cell Burden and TIM-3 Expression with Recalcitrant Chronic Rhinosinusitis with Nasal Polyps

Abstract: Objectives: Previous work showed that higher polyp mast cell load correlated with worse postoperative endoscopic appearance in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). Polyp epithelial mast cells showed increased expression of T-cell/transmembrane immunoglobulin and mucin domain protein 3 (TIM-3), a receptor that promotes mast cell activation and cytokine production. In this study, CRSwNP patients were followed post-operatively to investigate whether mast cell burden or TIM-3 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, MCs infiltrating nasal polyps have been shown to have increased expression of T-cell/transmembrane immunoglobulin and mucin domain protein 3 (TIM-3), a receptor that promotes MC activation and production of cytokines [34]. Chronic inflammation underlying CRSwNP could be promoted and propagated at the epithelial cell layer and perhaps mediated by errone-ous initiation of signaling cascades, leading to TIM-3-mediated MC activation and degranulation.…”
Section: Crswnp: Mast Cell Endotypementioning
confidence: 99%
“…In addition, MCs infiltrating nasal polyps have been shown to have increased expression of T-cell/transmembrane immunoglobulin and mucin domain protein 3 (TIM-3), a receptor that promotes MC activation and production of cytokines [34]. Chronic inflammation underlying CRSwNP could be promoted and propagated at the epithelial cell layer and perhaps mediated by errone-ous initiation of signaling cascades, leading to TIM-3-mediated MC activation and degranulation.…”
Section: Crswnp: Mast Cell Endotypementioning
confidence: 99%
“…The latter is a common inducer of mucus, and it is postulated that these specific MCs might play a central role in mucus hypersecretion, which is frequently observed in CRSwNP patients [ 156 ]. Nasal polyps infiltrated by MCs express higher T cell immunoglobulin and mucin domain protein 3 (TIM-3), a receptor that promotes MCs activation and cytokine production [ 159 ]. Despite the higher expression of TIM-3 in the epithelium than in the stroma of nasal polyps, the infiltration of MCs into the stromal layer is associated with the severity of CRSwNP and resistance to medical and surgical treatments [ 160 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the degree of eosinophilic infiltration is widely recognized as one of the main indicators of severity and predictors of relapse and several biomarkers of eosinophilic inflammation have been identified ( 21 ). NC has shown that not only eosinophils but also mast cells are involved in contributing to the severity of the disease, orchestrating the inflammation underlying CRSwNP and producing a series of type 2 inflammatory cytokines ( 22 ). This cytologic point of view is of utmost importance, since in the era of Precision Medicine, several biological agents have been approved or are under evaluation for the treatment of CRSwNP ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%